2019
DOI: 10.21203/rs.2.11407/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kidney Outcome in Primary Focal Segmental Glomerulosclerosis (FSGS) by Using a Predictive Model

Abstract: Background: Focal segmental glomerulosclerosis (FSGS) is one of the important causes of end stage kidney disease (ESKD). We evaluated the risk factors of progression of primary FSGS to chronic kidney disease (CKD) or ESKD with a predictive model including clinical and histological predictors. Methods: 201 patients with primary FSGS (59% male, mean age: 38±15 years), were studied. Time-dependent Cox model and C statistics were used for the predictive model. Interaction and correlation between independent variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Even though the morphologic data in kidney biopsies appeared to be similar between the patients with ARN who did recover and those who did not recover from the episode of ARN, interstitial fibrosis and tubular atrophy was associated with increased serum creatinine levels at 12-month follow up for all patients, which corresponds with previously published data. 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Even though the morphologic data in kidney biopsies appeared to be similar between the patients with ARN who did recover and those who did not recover from the episode of ARN, interstitial fibrosis and tubular atrophy was associated with increased serum creatinine levels at 12-month follow up for all patients, which corresponds with previously published data. 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that impaired renal function, hypertension, and large amount of proteinuria upon diagnosis [34][35][36] as well as not response to the treatments of steroid and immunosuppressive agents were associated with progressive diseases and poor renal survival in patients with FSGS [13,20,34,37,38]. In addition, progression of FSGS disease was shown to be associated with different pathological features based on the Columbia FSGS classification [19], in which collapsing FSGS had a poorer renal survival rate and much rapid progression to ESKD compared to patients with NOS and tip variant with best renal survival rate in tip variant [11,20,38,39]. However, a recent study reported no significant difference in the progression of ESKD among different pathological FSGS variants [21].…”
Section: Comparison To Existing Modelmentioning
confidence: 99%